Critical Reading of Media News. Analysis of the Conflict between Media and Social Representations, Based on the Example of Slovenian Media - Kraner, David (Studia Gdańskie, 2023)
Media content is not bare facts, but media representations. The latter are often distortions of the truth. They must therefore be interpreted critically. This requires a lot of personal effort and knowledge about the topic, but at the same time a professional professional expertise of the media content. For this reason, most users do not analyse media content, but interpret it intuitively or take it literally. Research shows that the negative topics with which the media most often associate the Church are sexual abuse, money and politics. Such sensational topics capture the attention of users and positive topics are left out in the media. In the present study, the topics and connotations of the articles were analysed. We find that serious socio-political issues related to the church are neglected in the media. How and to what extent should the Catholic Church respond to such media portrayals, how do Church documents encourage media engagement and how can critical reading of media portrayals be encouraged?